Multi-site study on extension practices in the Family Health area (Research, Society and Development, 2025)
The general objective is to adress extension practices around family heath. Four cases were selected from the national literature on the central theme of the study. It can be considered that extension practices provide university students with rich experiences that add value to their respective education. It is understood that, based on the four cases analyzed from the literature, extension projects in health generate benefits not only for students, but also for the community. This consists of a moment of sharing knowledge, where good health and prevention practices are disseminated. Given the relevance of education of students in courses in health,, it is understood that universities should make efforts to improve their respective extension practices, in a dimension that is connected to the social dimension of the work of students and future graduates with the community.